If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5z + -18z = 39 Combine like terms: 5z + -18z = -13z -13z = 39 Solving -13z = 39 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Divide each side by '-13'. z = -3 Simplifying z = -3
| 3(2r-4)-2(r+4)= | | 14x-15=-13 | | 7r+8=9r+14 | | -23x+17y=-7 | | |x-1/5|=3 | | 6x(x+2)=6 | | 6x+10=4x+84 | | 2a-3b=2a-3b | | 208=-w+143 | | x-1/x-5=x-2/x-6 | | 116-y=263 | | -u+158=109 | | 3m-15form=7 | | tan^3x=3tanx | | f(x)=1/5×-2 | | 5x^2-y^16=0 | | f(x)=25+x | | Y^2-2y=3 | | y=10+5.112 | | 3e^2x=19 | | f(x)=-2x+4x | | -9x+5=114 | | (-4x^2)(5x^2)=80x | | 2=m/2-7 | | y=5x^2+13x-6 | | (6x+20)= | | 2-(x+5)=3x+9 | | 6(n-2)=36 | | (8/11)/(6/55) | | 8/11/6/55 | | j-77=6 | | 3x=2y+27 |